2022
DOI: 10.20944/preprints202209.0143.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<em>Cannabis sativa</em> CBD Extract Exhibits Synergy with Broad-Spectrum Antibiotics against <em>Salmonella typhimurium</em>

Abstract: New generation antibiotics are needed to combat the development of resistance to antimicrobials. One of the most promising new classes of antibiotics is cannabidiol (CBD). It is a non-toxic and low-resistance chemical that can be used to treat bacterial infections. The antibacterial activity of Cannabis sativa L. byproducts, specifically CBD, has been of growing interest in the field of novel therapeutics. As research continues to define and characterize the antibacterial activity that CBD possesses against a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Typhimurium ( 8 ), and in a separate publication, we also revealed that CBD synergizes with ampicillin and polymyxin B in killing S . Typhimurium (( 47 )). E34 phage protected Vero cells from Salmonella infection ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium ( 8 ), and in a separate publication, we also revealed that CBD synergizes with ampicillin and polymyxin B in killing S . Typhimurium (( 47 )). E34 phage protected Vero cells from Salmonella infection ( 38 ).…”
Section: Discussionmentioning
confidence: 99%